Mono and hybrid nanofluid analysis over shrinking surface with thermal radiation: A numerical approach - S. Saleem; Bilal Ahmad; Azra Naseem; Muhammad Bilal Riaz; Tasawar Abbas (Case Studies in Thermal Engineering, 2024)
The study of magnetohydrodynamics (MHD) incompressible flow of a fluid having hybrid nanoparticles making the colloidal combination with base fluid is presented in this research. Comparative analysis is carried out for the nanofluids Al2O3/Kerosene and ZnO/Kerosene oil with the hybrid nanofluid Al2O3–ZnO/Kerosene oil. The subject flows are influenced with thermal radiation and viscous dissipation. A numerical technique Keller box is employed to examine the envision mathematical model. For computational procedure MATLAB software will be used. Tabulated and graphical outcomes of different effects are presented for the appraisal of velocity and temperature distributions. It is comprehend that the thermal radiation and viscous dissipation parameters possess up surging trends for the hybrid and nanofluid temperature profile but opposite trend has been observed for different volume fractions of nanoparticles.